Prognostic factors in Merkel cell carcinoma patients undergoing sentinel node biopsy. Issue 8 (August 2017) - Mattavelli, I.; Patuzzo, R.; Torri, V.; Gallino, G.; Maurichi, A.; Lamera, M.; Valeri, B.; Bolzonaro, E.; Barbieri, C.; Tolomio, E.; Moglia, D.; Nespoli, A.M.; et al.
Abstract: Introduction: Debate remains about prognostic factors in primary Merkel cell carcinoma (MCC). We investigated clinicopathological factors as determinants of survival in patients with MCC submitted to sentinel node biopsy. Methods: Sixty-four consecutive patients treated for a primary MCC were identified from a prospectively maintained database at Fondazione IRCCS Istituto Nazionale dei Tumori, Milan. Time to events outcome were described by product limit estimators and proportional hazards model was used to investigate the association between outcome and potential predictors. Results: The most common site of primary tumor was lower limbs (56.3%). The size of primary lesion was ≤2 cm in 67.2% of cases. Presence of residual disease after the diagnostic surgical excision was observed in 28% of cases. All patients received sentinel node biopsy (SNB) and a SN positivity was detected in 26.6%. The median follow up was 78 months. Disease recurrence occurred in 17 patients (26.6%). In the SN negative group 10 recurrences occurred (21.3%), whereas 7 (41.2%) were found in SN positive one. Nine patients SN negative (19.1%) died of disease and 3 (17.6%) among SN positive. SN status was not associated with survival (p = 0.78). Neither age, gender, size and site of primary tumor resulted predictors of patients' outcome. The presence of residual tumor in the specimen of the wide local excision, after the diagnostic surgical excision, was the only variable associated with survival (p = 0.03). Conclusions: Presence of residual tumor in the specimen of the wide local excision is the main prognostic factor in MCC patients.